PENGEMBANGAN MODUL AJAR ELEKTRONIK BERBASIS PjBL BERBANTUKAN APLIKASI KODULAR PADA MATERI VIRUS UNTUK KELAS X FASE E SMA - Yulia Ratna Sari; Yoko Masna Rivan. M (LPPM Universitas Cipta Mandiri, 2024)
This research aims to create an electronic teaching module for high school phase E students based on project-based learning about viruses. This kind of study uses a 4-D model for research and development. The four phases of the 4-D model are definition, design, development, and dissemination. The 4-D model is modified in this study for the validation stage of development. Eight high school teachers and two biology lecturers made up the research subjects. Using a modular application, an electronic teaching module for viral material based on project-based learning is the research object. A validity question naireisusedas the data-gathering tool. The average value of the language expert assessmentis 89.58% very good credentials, and the average value of the material expert assessment is 88.27% very good qualifications, according to the research findings. The expert evaluation assessment has 80.00% good credentials, the media expert assessment has 86.19% very good qualifications, and the teaching equipment expert assessment has 95.13% very good qualifications. With very good credentials, then tire average validity value is 87.83%. Wemay infer that anelectronic teaching modul efor high school phase E students based on project-based learning about viruses has been created using very reliable criteria and is appropriate for usage.